The complete chloroplast genome sequence of Catalpa fargesii f. duclouxii (Bignoniaceae) - Wen-Jun Ma; Song-Zhi Xu; Gui-Juan Yang; Ying Liu; Xiao-Guo Xiang; Jun-Hui Wang (Mitochondrial DNA. Part B. Resources, 2020)
The complete chloroplast genome sequence of Catalpa fargesii f. duclouxii C.A. May was firstly assembled and analyzed in this study. The whole genome of this species was 158164 bp in length, with a typical quadripartite structure. The large single copy (LSC) was 83986 bp, the small single copy (SSC) was 12660 bp, and both of the two inverted repeats (IRs) were 30259 bp, respectively. A total of 134 genes in the chloroplast genome were annotated, including 87 protein-coding genes, 8 ribosomal RNA (rRNA) genes, and 39 transfer RNA (tRNA) genes. The phylogenetic analysis showed that C. fargesii f. duclouxii was highly clustered with C. bungei.